Standard operating procedure to prepare agar phantoms. (July 2016) - Souza, R M; Santos, T Q; Oliveira, D P; Souza, R M; Alvarenga, A V; Costa-Felix, R P B
Abstract: Agar phantoms are widely used as soft tissue mimics and some preparation techniques are described in the literature. There are also standards that describe the recipe of a soft tissue mimicking material (TMM). However some details of manufacture process are not clearly defined. The standardization of the phantom's preparation can produce a metrological impact on the results of the acoustic properties measured. In this direction, this paper presents a standard operating procedure (SOP) to prepare the agar TMM described on the IEC 60601-237.